A new species of Centrozoros Kukalová-Peck & Peck, 1993 (Zoraptera: Spiralizoridae) from high elevations in the northwestern Andes of Colombia - Lima, Sheila P.; Oliveira, Ismael B.; Mazariegos, Luis A.; Fernandes, Daniell R. R.; Rafael, José A. (Zootaxa, 2024)
This study aims to expand the knowledge of angel insects in Colombia. A new species of Centrozoros Kukalová-Peck & Peck, 1993 (Zoraptera: Spiralizoridae) from a high elevation area of Colombia is described. Centrozoros mesenia Lima, Oliveira & Rafael sp. nov. was collected from Andean cloud forest at the Mesenia-Paramillo Nature Reserve. The new species is described based on a male specimen and is characterized mainly by the presence of a leaf-like sclerotized projection at the base of the aedeagus. We present digital images of the new species and a distribution map of the species of Zoraptera registered for Colombia until now.